Prognozowanie cen żywca wieprzowego z wykorzystaniem modeli zgodnych i zmiennych wyprzedzających - Hamulczuk, Mariusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
The aim of the research is to examine possibilities of application congruent models based on the leading variables in the pig prices short-time forecasting in Poland. The main way of assessment of the suitability of these methods in predicting the future was the ex post analysis. According to the research the shortterm forecast based on those models are more accurate those based on the professionals opinion.